2023
DOI: 10.1007/s10337-023-04250-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of UPLC-MS/MS Method for Analysis of Apigenin, Apigenin 7-Glucoside and Chlorogenic Acid in Goat Serum

Abstract: UPLC-MS/MS method was developed for determination of bioactive compounds including chlorogenic acid (CA), apigenin (AP) and apigenin 7-glucoside (AP7G) in goat serum. The analytes were separated on Kinetex C18 analytical column and a mobile phase consisting 0.1% formic acid in water and methanol with gradient elution. Detection of analytes was performed using a triple quadrupole mass spectrometer with electrospray ionization in positive mode. The lower limit of quantitation was 0.5 ng mL–1 for AP and AP7G and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The results of the sensory evaluation are presented in the graph in Figure 10. From a practical point of view, the results of the assessment are very promising, as they allow the use of the pro-health effect of the herbal mixtures tested in this study [12,13] without significance, except for the reduced intensity of the goaty smell, modification of the taste and smell of the produced milk.…”
Section: Sensory Quality Of Milkmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of the sensory evaluation are presented in the graph in Figure 10. From a practical point of view, the results of the assessment are very promising, as they allow the use of the pro-health effect of the herbal mixtures tested in this study [12,13] without significance, except for the reduced intensity of the goaty smell, modification of the taste and smell of the produced milk.…”
Section: Sensory Quality Of Milkmentioning
confidence: 89%
“…Studies conducted on goats showed that herbal supplements have a positive effect on the digestive processes of the goats and increasing the colonies of lactic acid bacteria (LAB) that fortify microbial homeostasis in the gastro-intestinal tract [12]. Other results revealed a significant effect of herbal supplements on the concentration of biologically active substances, such as apigenin, apigenin 7-glucoside and chlorogenic acid, in goat serum [13]. Another interesting result related to modifying goat milk's fatty acid profile by adding fenugreek grain to goats' diet [14].…”
Section: Introductionmentioning
confidence: 99%